2017
DOI: 10.1101/208330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Germline determinants of the somatic mutation landscape in 2,642 cancer genomes

Abstract: Cancers develop through somatic mutagenesis, however germline genetic variation can markedly contribute to tumorigenesis via diverse mechanisms. We discovered and phased 88 million germline single nucleotide variants, short insertions/deletions, and large structural variants in whole genomes from 2,642 cancer patients, and employed this genomic resource to study genetic determinants of somatic mutagenesis across 39 cancer types. Our analyses implicate damaging germline variants in a variety of cancer predispos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 88 publications
2
33
0
Order By: Relevance
“…While another study has linked specific mutagenic consequences of germline variants to the somatic mutation signatures, such as, BRCA1/2 with signature 3 (DNA double strand breaks) and APOBEC3A/3B germline variants with APOBEC specific somatic mutation signatures. 46 Interestingly, our study identified APOBEC mutational signatures as the main non-UVR-related mutagenic process at work in AYA melanomas, without any germline variants to the aforementioned genes. However, the study identified a germline RAD50 variation in the NF1 mutated case (MELA_35619), of which APOBEC was the greatest non-UVR contributing mutagenic process in this patient's melanoma.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…While another study has linked specific mutagenic consequences of germline variants to the somatic mutation signatures, such as, BRCA1/2 with signature 3 (DNA double strand breaks) and APOBEC3A/3B germline variants with APOBEC specific somatic mutation signatures. 46 Interestingly, our study identified APOBEC mutational signatures as the main non-UVR-related mutagenic process at work in AYA melanomas, without any germline variants to the aforementioned genes. However, the study identified a germline RAD50 variation in the NF1 mutated case (MELA_35619), of which APOBEC was the greatest non-UVR contributing mutagenic process in this patient's melanoma.…”
Section: Discussionmentioning
confidence: 68%
“…This does not seem to be the case in the AYA melanomas, as none of the AYA cases harbored germline variants in these genes. While another study has linked specific mutagenic consequences of germline variants to the somatic mutation signatures, such as, BRCA1/2 with signature 3 (DNA double strand breaks) and APOBEC3A/3B germline variants with APOBEC specific somatic mutation signatures . Interestingly, our study identified APOBEC mutational signatures as the main non‐UVR‐related mutagenic process at work in AYA melanomas, without any germline variants to the aforementioned genes.…”
Section: Discussionmentioning
confidence: 99%
“…TraFiC-mem performs the actions described above in both, the tumour and the matched normal genomes. In order to remove potential germline calls, MEI candidates are filtered out from the tumour sample if: (a) they are located within 200 bp of a cluster from the same retrotransposon family in the matched normal sample that is supported by at least 3 reads; and/or (b) there is a polymorphic insertion from the same retrotransposon family within a range of 200 bp that is present in 'TraFiC-ip db' 7 , dbRIP 54 , the 1,000 Genomes Project Phase 3 callset 55,56 or the dataset of germline events identified by our group across PCAWG 22 . Finally, we noticed the existence of mapping artefacts leading to quite frequent false positive insertion calls (particularly in Alu and SVA calls), located within or between repeats of the same family in the reference genome.…”
Section: (I) Identification Of Mei Candidates Via Discordant Reads Anmentioning
confidence: 94%
“…Our observation of somatic second hit (Figure 2-3) and transcriptional effects (Figure 4) coupled with germline variants also adds on to the current literature on germline-somatic interactions in cancer [45]. While the majority of cancer genomic studies focus exclusively on the germline or somatic genome, pathogenic germline variants are associated with different somatic mutational signatures, allele-specific imbalance, or somatic drivers [11,26,[46][47][48]. The availability of germline DNA analysis and tumor genomic and transcriptomic analyses from the same individual provides critical data to the analyses describe here that is not possible in many studies that only analyze germline DNA samples alone.…”
Section: Discussionmentioning
confidence: 75%